Participatory evaluation on the introduction of leguminous cover crops in slash and mulch systems for sustainable corn production in the Toledo district, Belize - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This document is a final report that contains information about the project: Participatory evaluation on the introduction of leguminous cover crops in slash and mulch systems for sustainable corn production in the Toledo district, Belize, its objectives and results are analyzed.